The K+ channel GIRK2 is both necessary and sufficient for peripheral opioid‐mediated analgesia. Issue 8 (1st July 2013) - Nockemann, Dinah; Rouault, Morgane; Labuz, Dominika; Hublitz, Philip; McKnelly, Kate; Reis, Fernanda C.; Stein, Christoph; Heppenstall, Paul A.
<x xml:space="preserve">Abstract</x> The use of opioid agonists acting outside the central nervous system (CNS) is a promising therapeutic strategy for pain control that avoids deleterious central side effects such as apnea and addiction. In human clinical trials and rat models of inflammatory pain, peripherally restricted opioids have repeatedly shown powerful analgesic effects; in some mouse models however, their actions remain unclear. Here, we investigated opioid receptor coupling to K+ channels as a mechanism to explain such discrepancies. We found that GIRK channels, major effectors for opioid signalling in the CNS, are absent from mouse peripheral sensory neurons but present in human and rat. In vivo transgenic expression of GIRK channels in mouse nociceptors established peripheral opioid signalling and local analgesia. We further identified a regulatory element in the rat GIRK2 gene that accounts for differential expression in rodents. Thus, GIRK channels are indispensable for peripheral opioid analgesia, and their absence in mice has profound consequences for GPCR signalling in peripheral sensory neurons.